The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1037/rmh0000002
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities associated with rural mental health practice.

Abstract: This manuscript outlines the challenges and opportunities associated with rural mental health practice, and provides descriptive data on the scope of care, area of competence, and clinical training of a group of practitioners providing services in rural central Appalachia. Thematic content analysis reveals ethical challenges encountered, job satisfaction, and the pinnacles and pitfalls of mental health care practice in the region. Implications for training, recruiting, and retaining practitioners to work in un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 38 publications
2
55
0
Order By: Relevance
“…Rural school counselors may be the only mental health professional troubled students see; however, these counselors are often constrained in their response to mental health concerns because of stigma, inadequate referral options, and the limited way their roles are construed, and these limitations can impact social-emotional well-being, education, and career development (Hastings & Cohn, 2013;Saba, 1991). In addition, there is a structural reality that affects all students: school counselors' formal role with emerging adults ends just as that life stage begins.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Rural school counselors may be the only mental health professional troubled students see; however, these counselors are often constrained in their response to mental health concerns because of stigma, inadequate referral options, and the limited way their roles are construed, and these limitations can impact social-emotional well-being, education, and career development (Hastings & Cohn, 2013;Saba, 1991). In addition, there is a structural reality that affects all students: school counselors' formal role with emerging adults ends just as that life stage begins.…”
Section: Literature Reviewmentioning
confidence: 98%
“…In addition, there is a structural reality that affects all students: school counselors' formal role with emerging adults ends just as that life stage begins. School counselors are vested with building an on-ramp to a bridge, but their work stops at the edge of the water (Hastings & Cohn, 2013;Saba 1991).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rural residents face challenges in finding transportation to facilities for professional care. Consequently, rural residents often forgo attaining adequate and timely mental health treatment (Alang, 2015;Hastings & Cohn, 2013). Rural residents often depend on alternative sources such as faith-based organizations to address mental health concerns (Bryant, Moore, Willis, & Hadden, 2015) or ignore the prevalence of mental health symptomology altogether (Snell-Rood et al, 2017).…”
Section: Mental Health In Rural Areasmentioning
confidence: 99%
“…Rural residents often depend on alternative sources such as faith-based organizations to address mental health concerns (Bryant, Moore, Willis, & Hadden, 2015) or ignore the prevalence of mental health symptomology altogether (Snell-Rood et al, 2017). Unfortunately, researchers indicated that rural residents seek treatment for mental health disorders after they have become progressively worse, resulting in more extensive treatment, which is often unavailable or costly for rural clients (Gore, Sheppard, Waters, Jackson, & Brubaker, 2016;Hastings & Cohn, 2013;Snell-Rood et al, 2017). Deen and Bridges (2011) suggested these delays in seeking mental health treatment are associated with low MHL.…”
Section: Mental Health In Rural Areasmentioning
confidence: 99%
See 1 more Smart Citation